1986
DOI: 10.1111/j.1600-0404.1986.tb04604.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased glutathione peroxidase activity in erythrocytes in patients with Alzheimer's disease/senile dementia of Alzheimer's type

Abstract: Glutathione peroxidase (GSH-Px) activity in erythrocytes was studied in 9 patients with Alzheimer's disease/senile dementia of Alzheimer's type (AD/SDAT) of ages 34-64 years and compared with that in 16 healthy controls of ages 21-66 years. The median GSH-Px activity in erythrocytes from AD/SDAT patients was 408, mu kat/1 (range 338-500 mu kat/1) and that from healthy controls 348, mu kat/1 (range 258-439 mu kat). This difference was significant (p less than 0.005) Wilcoxon rank test. Since there are great cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 21 publications
3
14
2
2
Order By: Relevance
“…This result may be explained by the fact that cellular and extracellular media contain different isoenzymes [21,22] or by the high variability of plasma composition. The results we obtained on erythrocytes are partly consistent with the data of Anneren et al [23] who found an increased activity of GPx in erythrocytes of 9 senile DAT/DAT patients in comparison to 16 healthy con trols. Conversely, Sulkawa et al [10] ob served no change in erythrocyte GPx and SOD in patients with Alzheimer's disease as compared with 5 controls, but these authors examined small series of patients.…”
Section: Discussionsupporting
confidence: 82%
“…This result may be explained by the fact that cellular and extracellular media contain different isoenzymes [21,22] or by the high variability of plasma composition. The results we obtained on erythrocytes are partly consistent with the data of Anneren et al [23] who found an increased activity of GPx in erythrocytes of 9 senile DAT/DAT patients in comparison to 16 healthy con trols. Conversely, Sulkawa et al [10] ob served no change in erythrocyte GPx and SOD in patients with Alzheimer's disease as compared with 5 controls, but these authors examined small series of patients.…”
Section: Discussionsupporting
confidence: 82%
“…There is a significative decrease of GSH-Px in the patient group contrary to the study of Anneren et al [31] which concerned younger individuals. Like Burns and Holland [16], we observed a significant decrease of free and total vitamin E in serum (p < 0.03) in the patient group.…”
Section: Resultscontrasting
confidence: 54%
“…Moreover, it is well known that unconjugated bilirubin is the main form of the bile pigment endowed with antioxidant activity . Many other previous studies about the neurological disorders provide evidence for peripheral (plasma and RBC)-central relations of the indices of abnormal free radical metabolism and relations between peripheral measures of antioxidant defense system and CNS findings (Anneren et al, 1986;Zemlan et al, 1989;Subbarao et al, 1990;Reddy and Yao, 1996;Yao et al, 2000). The plasma unconjugated bilirubin levels are reflected in the plasma concentrations of total bilirubin.…”
Section: Discussionmentioning
confidence: 94%